The relation between reproduction of paintings and literary text in the Portuguese textbook (Revista Educação, Artes e Inclusão, 2024)
The importance of investigate the representations of paintings and it use is affirm when we testify with its immense quantity present in Portuguese textbooks. Our objective is to investigate how representations of paintings are being used in the Didactic Book “Contemporary Portuguese: dialogue, reflection and use” (PNLD 2018 to 2020). The term multimodality is present to understand the students training process, from the perspective of the relation between the verbal text and the non-verbal text. Methodologically, this work favors adocumental analysis, with an interpretive qualitative bias. This study is theoretically based on the following authors, namely: Barbosa (1989, 2003); Praz (1982); Pereira (2017), Joly (2007) and Maroun (2007). To analyze the function of each painting representation, we created categories of analysis, based on Torreão, 2014, which pointed out the different perspectives on the function of each one of them. Thus, we found that the representations of paintings fulfill the function of an immature, inconsistent and disconnected illustration, marking the production of meaning, which implies a hierarchy between the verbal and the picture text. The representations of paintings, present in textbooks, need to be read and / or explored in their communicative, semiotic and aesthetic dimensions.
Keywords: representation of painting; literature; portuguese textbook; multimodal text